Sustainable development model toward environmentally friendly hospital - F, Aini; A. Irianto; S. Amar (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This study aims to create an environmentally friendly hospital at West Pasaman regional public hospital by implementing a sustainable development model, which consists of the green hospital, green building, green innovation, and green human resource management. The researchers previously discussed the physical aspects of the building, efficiency related to energy saving and hospital waste management. However, from several references obtained, it has not yet been discussed what is the extent of the benefits derived from the entire implementation of the green hospital. Thus, this study contributes to creating an environmentally friendly hospital model mediated by a green hospital and it is influenced by green building, green innovation, and green human resource management.METHODS: The study method uses a survey, which uses a questionnaire as a data collection tool. The population in this study consisted of employees, visitors, and the community around West Pasaman regional public hospital. The selection of the sample in this study was based on the proportionate cluster random sampling approach, which was analyzed using the structural equation modeling–partial least square method.FINDINGS: There are ten findings for analysis at the West Pasaman regional public hospital. First, green building has a significant effect of 0.187 on the green hospital. Second, green innovation has a significant effect of 0.230 on the green hospital. Third, green human resource management has a significant effect of 0.235 on the green hospital. Fourth, green building has a significant effect of 0.263 on the environmentally friendly hospital. Fifth, green innovation has a significant effect of 0.192 on the environmentally friendly hospital. Sixth, green human resource management has a significant effect of 0.197 on the environmentally friendly hospital. Seventh, the green hospital has a significant effect of 0.241 on the environmentally friendly hospital. Eighth, green building has a significant effect of 0.045 on the environmentally friendly hospital mediated by the green hospital. Ninth, green innovation has a significant effect of 0.055 on the environmentally friendly hospital mediated by the green hospital. Tenth, green human resource management has a significant effect of 0.057 on the environmentally friendly hospital mediated by the green hospital.CONCLUSION: Implementation of the sustainable development model as a form of environmental management policy at the West Pasaman regional public hospital is optimally needed in order to achieve an environmentally friendly hospital. This study recommends employees, visitors the community around the West Pasaman regional public hospital to increase the green hospital, green building, green innovation, and green human resource management in achieving an environmentally friendly hospital.